Development of Domestication Technology for Wader Puntius binotatus in the Brantas River Watershed, East Java - Ferawati, Yunetta; Khusaini, Moh.; Parmawati, Rita; Efani, Anthon (Journal of Ecohumanism, 2025)
Puntius binotatus Wader fish in the Brantas Watershed (DAS) have an important position in society because in addition to being consumed, they are also bioindicators of the health level of public waters. The purpose of this study was to formulate a suitable domestication technique for Puntius binotatus Wader fish in the Brantas Watershed area of East Java. This type of research can be categorized as development research, also known as research and development (R&D). The outcome produced in this study is a sustainable management model for domestication of Wader fish in the Brantas Watershed, East Java. The domestication process of Wader fish was analyzed descriptively, including the stages in the domestication process of Wader fish which are wild fish so that they can be cultivated. Domestication, in addition to preventing extinction, this technology has potential in fisheries businesses. This process aims to increase productivity, control its life cycle, and ensure the availability of Wader fish throughout the year for consumption and conservation. The domestication of Wader fish requires preparation in two key areas: (1) studying their biological characteristics, including morphology, habitat, and distribution; and (2) understanding their reproductive characteristics, including sex differentiation, gonadal maturity, and fecundity.